HUBUNGAN STATUS AKREDITASI PUSKESMAS DENGAN MUTU PELAYANAN DI KABUPATEN SIMALUNGUN - Siti Marlina; Novrika Silalahi; Septa Dwi Insani; Herri Novita Tarigan; Friska Ernita Sitorus (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2020)
Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts, with greater emphasis on promotive and preventive efforts, to achieve the highest level of public health in the working area. Puskesmas Accreditation is an acknowledgment given by an independent Accreditation provider established by the Minister after meeting Accreditation standards. The purpose of this study was to determine the relationship between Puskesmas Accreditation Status and Service Quality in Simalungun District. This type of research is analytic to determine the relationship between Puskesmas Accreditation Status and Service Quality in Simalungun District. This study uses a case control study approach (case and control), where independent variables are determined first, then the dependent variable is searched through a questionnaire that has been tested. A sample of 92 people, 46 were sampled for cases (Puskesmas Tiga Dolok) and 46 for controls (puskesmas Huta Bayu) using consecutive sampling techniques. Based on the results of bivariate test studies, that the dimensions of service quality related to the health center accreditation status (p <0.05) are tangibles, reliability, responsiveness, and assurance dimensions. Factors that are not related to the health center accreditation status (p> 0.05) are empathy dimensions. From the multivariate test results, it is known that the most dominant factor on the status of puskesmas accreditation is the quality of service based on the dimensions of responsiveness.